Developmental nicotine exposure alters potassium currents in hypoglossal motoneurons of neonatal rat - Cholanian, Marina (J Neurophysiol, 2017)
We previously showed that nicotine exposure in utero and after birth via breast milk [developmental nicotine exposure (DNE)] is associated with many changes in the structure and function of hypoglossal motoneurons (XIIMNs), including a reduction in the size of the dendritic arbor and an increase in cell excitability. Interestingly, the elevated excitability was associated with a reduction in the expression of glutamate receptors on the cell body. Together, these observations are consistent with a homeostatic compensation aimed at restoring cell excitability. Compensation for increased cell excitability could also occur by changing potassium conductance, which plays a critical role in regulating resting potential, spike threshold, and repetitive spiking behavior. Here we test the hypothesis that the previously observed increase in the excitability of XIIMNs from DNE animals is associated with an increase in whole cell potassium currents. Potassium currents were measured in XIIMNs in brain stem slices derived from DNE and control rat pups ranging in age from 0 to 4 days by whole cell patch-clamp electrophysiology. All currents were measured after blockade of action potential-dependent synaptic transmission with tetrodotoxin. Compared with control cells, XIIMNs from DNE animals showed significantly larger transient and sustained potassium currents, but this was observed only under conditions of increased cell and network excitability, which we evoked by raising extracellular potassium from 3 to 9 mM. These observations suggest that the larger potassium currents in nicotine-exposed neurons are an important homeostatic compensation that prevents “runaway” excitability under stressful conditions, when neurons are receiving elevated excitatory synaptic input. NEW & NOTEWORTHY Developmental nicotine exposure is associated with increased cell excitability, which is often accompanied by compensatory changes aimed at normalizing excitability. Here we show that whole cell potassium currents are also increased in hypoglossal motoneurons from nicotine-exposed neonatal rats under conditions of increased cell and network excitability. This is consistent with a compensatory response aimed at preventing instability under conditions in which excitatory synaptic input is high and is compatible with the concept of homeostatic plasticity.